Multidimensional regulation of estrogen signaling in pelvic floor connective tissue homeostasis and remodeling - Wang, Lin; Geng, Mengyu; Wei, Lingyun; Wang, Shuyu; Wang, Wenzhen; Liu, Xiaochun (Frontiers in Immunology, 2026)
Pelvic organ prolapse (POP) is a prevalent condition that significantly impairs women’s quality of life and is closely linked to dysregulated estrogen signaling. This review examines the mechanisms through which estrogen, acting via nuclear receptors (ERα and ERβ) and the membrane receptor G protein-coupled estrogen receptor (GPER), regulates pelvic floor connective tissue homeostasis through both genomic and non-genomic pathways. Key regulatory effects include the promotion of collagen and elastin synthesis, inhibition of matrix metalloproteinase (MMP) activity, modulation of fibroblast function—including mitigation of cellular senescence and enhancement of migratory and anti-apoptotic capacities—as well as integration with mechanical signaling through the integrin-YAP/TAZ axis. Additionally, estrogen helps suppress chronic inflammation and influences macrophage polarization. Clinical evidence indicates that estrogen deficiency and an elevated ERα/ERβ ratio contribute to extracellular matrix degradation, a hallmark of POP. Although local estrogen therapy can improve perioperative tissue quality, its long-term efficacy in structural restoration remains limited. Emerging therapeutic approaches include selective estrogen receptor modulators, ERβ-specific agonists, and personalized interventions based on receptor profiling and genetic markers. Future research should leverage patient-derived organoid models and targeted drug delivery platforms to decipher individual pathophysiology and translate findings into precise interventions.